Decadal Region-Wide and Glacier-Wide Mass Balances Derived from Multi-Temporal ASTER Satellite Digital Elevation Models. Validation over the Mont-Blanc Area - Berthier, Etienne; Cabot, Vincent; Vincent, Christian; Six, Delphine (Frontiers in Earth Science, 2016)
Since 2000, a vast archive of stereo-images has been built by the Advanced Spaceborne Thermal Emission and Reflection (ASTER) satellite. Several studies already extracted glacier mass balances from multi-temporal ASTER digital elevation models (DEMs) but they lacked accurate independent data for validation. Here, we apply a linear regression to a time series of 3D-coregistered ASTER DEMs to estimate the rate of surface elevation changes (dh/dtASTER) and geodetic mass balances of Mont-Blanc glaciers (155 km²) between 2000 and 2014. Validation using field and spaceborne geodetic measurements reveals large errors at the individual pixel level (> 1 m a-1) and an accuracy of 0.2-0.3 m a-1 for dh/dtASTER averaged over areas larger than 1 km². For all Mont-Blanc glaciers, the ASTER region-wide mass balance (-1.05±0.37 m water equivalent (w.e.) a-1) agrees remarkably with the one measured using Spot5 and Pléiades DEMs (-1.06±0.23 m w.e. a-1) over their common 2003-2012 period. This multi-temporal ASTER DEM strategy leads to smaller errors than the simple differencing of two ASTER DEMs. By extrapolating dh/dtASTER to mid-February 2000, we infer a mean penetration depth of about 9±3 m for the C-band Shuttle Radar Topographic Mission (SRTM) radar signal, with a strong altitudinal dependency (range 0-12 m). This methodology thus reveals the regional pattern of glacier surface elevation changes and improves our knowledge of the penetration of the radar signal into snow and ice.